Multiproperties of New Schiff Base and Its Mononuclear Copper(II) Complex. Synthesis, Characterization, Liquid Crystal Properties and Antioxidant Activities - Yorur-Goreci, Cigdem; Altas-Kiymaz, Nilay; Peksel, Aysegul; Bilgin-Eran, Belkiz (CHEM SOC PAKISTAN, 2012)
A new Schiff base ligand, 4-(octadecyloxy)-N-(4-hexyloxyphenyl)-2-hydroxybenzalimine (3), was synthesized by condensation of 4-octadecyloxy-2-hydroxybenzaldehyde with 4-hexyloxyaniline. This ligand have been characterized by UV-VIS, FTIR, H-1-NMR, C-13-NMR, mass spectra. Copper(II) complex (4) of this ligand has been prepared by the interaction of copper(II) acetate dihydrate with ethanolic solution of the ligand. The copper(11) complex was confirmed by various spectroscopic studies like UV-VIS, FTIR and elemental analysis. The liquid crystalline behaviour of the ligand and copper(II) complex was determined by polarized light microscopy (PM) and differantial scanning calorimetry (DSC). The antioxidant activities of the free Schiff base and its complex have been investigated with different tests such as 2,2-diphenyl-1-picrylhydrazyl (DPPH center dot), superoxide, 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS(center dot+)) and N,N-dimethyl-p-phenylenediamine dihydrochloride (DMPD center dot+) radical scavenging activities. The results were compared with known antioxidants e.g. butylated hydroxyanisole (BHA), butylated hydroxytoluene (BHT), trolox, alpha-tocopherol or ascorbic acid. The ligand exhibited different levels of antioxidant activity in all tests. Therefore, some activities were pressurized in the its copper(II) complex.
Keywords: Schiff bases; Cu(II) complexes; Liquid crystals; Antioxidant activity; Radical scavenging ability; METAL-COMPLEXES; IMINES; Chemistry